1996
DOI: 10.1063/1.117776
|View full text |Cite
|
Sign up to set email alerts
|

New features of the layer-by-layer deposition of microcrystalline silicon films revealed by spectroscopic ellipsometry and high resolution transmission electron microscopy

Abstract: Spectroscopic ellipsometry and high resolution transmission electron microscopy have been used to characterize microcrystalline silicon films. We obtain an excellent agreement between the multilayer model used in the analysis of the optical data and the microscopy measurements. Moreover, thanks to the high resolution achieved in the microscopy measurements and to the improved optical models, two new features of the layer-by-layer deposition of microcrystalline silicon have been detected: ͑i͒ the microcrystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 7 publications
(10 reference statements)
0
30
0
Order By: Relevance
“…The preparation of the samples for cross sectional HTREM measurements has been previously described 10 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation of the samples for cross sectional HTREM measurements has been previously described 10 .…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies we have combined the LBL technique with in situ ellipsometry analysis of the film properties and validated the optical models with high-resolution transmission electron microscopy (HRTEM) 10 and secondary ion mass spectrometry measurements 11 . We showed that both surface and growth zone processes are involved in the growth of µc-Si:H [12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that in-situ spectroscopic UV-Visible ellipsometry is an excellent tool to characterize the composition of thin films such as microcrystalline silicon [16][17][18][19]. An in-situ UV-Visible spectroscopic ellipsometer (Jobin Yvon -MWR UVISEL) was used to measure the imaginary part of the pseudo-dielectric function (Im[ε]) of the epitaxial films deposited on the c-Si wafer at various stages of the process.…”
Section: Methodsmentioning
confidence: 99%
“…We used this technique to optimize the plasma cleaning conditions and as well the epitaxial silicon film growth. The thickness of the layers and their composition were determined by modeling the ellipsometry data using the Bruggemann effective medium approximation [16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%